Percutaneous Soft Tissue Release for Treating Chronic Recurrent Myofascial Pain Associated with Lateral Epicondylitis: 6 Case Studies. (2nd December 2012) - Lin, Ming-Ta; Chou, Li-Wei; Chen, Hsin-Shui; Kao, Mu-Jung
Abstract : Objective . The purpose of this pilot study is to investigate the effectiveness of the percutaneous soft tissue release for the treatment of recurrent myofascial pain in the forearm due to recurrent lateral epicondylitis. Methods . Six patients with chronic recurrent pain in the forearm with myofascial trigger points (MTrPs) due to chronic lateral epicondylitis were treated with percutaneous soft tissue release of Lin's technique. Pain intensity (measured with a numerical pain rating scale), pressure pain threshold (measured with a pressure algometer), and grasping strength (measured with a hand dynamometer) were assessed before, immediately after, and 3 months and 12 months after the treatment. Results . For every individual case, the pain intensity was significantly reduced ( P < 0.01 ) and the pressure pain threshold and the grasping strength were significantly increased ( P < 0.01 ) immediately after the treatment. This significant effectiveness lasts for at least one year. Conclusions . It is suggested that percutaneous soft tissue release can be used for treating chronic recurrent lateral epicondylitis to avoid recurrence, if other treatment, such as oral anti-inflammatory medicine, physical therapy, or local steroid injection, cannot control the recurrent pain.